2021
DOI: 10.1007/s43546-021-00099-w
|View full text |Cite
|
Sign up to set email alerts
|

Control of corruption, microfinance, and income inequality in MENA countries: evidence from panel data

Abstract: There has been a reduction in income inequality in the MENA region along with a dramatic deterioration in control corruption. In this regard, microfinance appears to be a potential factor that could contribute to reducing these inequalities in such region. This paper contributes to the literature in an attempt to understand the key role of microfinance and control of corruption in reducing income inequality in MENA countries using a panel data covering the period 1996-2018. To examine the relationships, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Batabyal and Chowdhury [31] conducted empirical analysis with panel data of 30 countries from 1995 to 2008, and found that corruption indirectly increases income inequality by inhibiting financial development. Using panel data covering the period 1996-2018 and MENA (Middle Eastern and Northern Africa) countries, Lassoued [32] found that a lower level of corruption is associated with less income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Batabyal and Chowdhury [31] conducted empirical analysis with panel data of 30 countries from 1995 to 2008, and found that corruption indirectly increases income inequality by inhibiting financial development. Using panel data covering the period 1996-2018 and MENA (Middle Eastern and Northern Africa) countries, Lassoued [32] found that a lower level of corruption is associated with less income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the This value is smaller than the lower Durbin-Watson limit, which means there is autocorrelation in the model. To overcome the autocorrelation problem that occurs, the model will be estimated using the Generalized Least Squares or GLS method where in this method it is assumed that the model is free from autocorrelation problems (Damodar, 2011;Lassoued, 2021;Shaikh et al, 2021).…”
Section: Multicollinearity Testmentioning
confidence: 99%
“…The immense obstacle in monetary increase and improvement (Park, 2012) and it exaggerates the hassle with NPLs while finances are channeling to awful tasks (Mohamad, & Jenkins, 2021;Mehmood, Hidthiir, & Nor, 2019;Toader, Onofrei, Popescu, & Andrieș, 2017;Bougatef, 2015) which usually finally ends up with a growing of NPLs (Kasinger et al, 2021;Taiwo, & Mike, 2021). Subsequently, corruption has an extreme hurdle to the powerful enlistment and division of the assets (Lassoued, 2021;Bougatef, 2015;The Global Economy., 2017). Corruption is a vital factor to decide the non-preforming loans (Hu et al, 2007) at the same time as Perk (2012) recognizes the corruption by way of an international element of the loan first-class within the banking quarter.…”
Section: Association Between Political Stability and Corruption On Nplsmentioning
confidence: 99%